Avaliação do desempenho dos tratamentos das superfícies dos meios filtrantes submetidos à filtração por pulso de ar reverso - Cirqueira, Samirys Sara Rodrigues (Universidade Federal de São Carlos, 2017)
The objective of this work was to characterize different fibrous filters after filtration and to evaluate the surface treatment performance of these materials during pulse jet filtration, in the removal of micrometric particles of dolomitic limestone. The filtration tests were performed maintaining the filtration velocity constant at 4 cm/s. The operating parameters of the cleaning media used were 200 ms and 2 kgf/cm2, corresponding to the cleaning pulse time and pressure, respectively. The experimental results were: residual pressure drop, cycle time, retained mass, cleaning and collection efficiency, particle deposition depth, deposited particle size, deposited particle size, permeability, porosity, thickness, roughness and diameter of the fibers of the filter media. Thus, in the comparison of fibrous filters of the same fiber (polyester fiber), the results presented different performances during the filtration due to the different surfaces, with untreated and treated (singeing/calendering and calendering/thermofixation). Untreated surface filters showed higher cleaning efficiency, lower residual pressure drop and increased permeability after fifty regenerations. However, greater wear on the fibers was observed. The fibrous filters with surface untreated showed close permeability values, lower cleaning efficiencies and higher residual pressure drop after 50 filter cycles. In addition, these fibrous filters with surface treated presented higher collection efficiency after the filtration cycles, in relation to the fibrous filter untreated surface. This indicates that the treatment on the surface of the filter medium is indispensable for cycles with long duration using the pulse jet cleaning. In the comparison of polyester and polypropylene fiber media subjected to the same treatment (calendering/thermofixation), the results showed a high cleaning efficiency in the initial cycles, but a reduction of the cleaning efficiency occurred with the increase of the filtration cycles. Furthermore, after the 100 filter cycles, the polyester fiber media showed higher cleaning efficiency, higher collection efficiency, lower particle retention (lower number and lower particle deposition depth), higher permeability, lower residual pressure and lower mass retained after the pulse jet cleaning in relation to PTFE immersion polypropylene media. It was also verified that, the polyester filter media, collected more particles on the surface, characterizing a surface filtration and a lower penetration of the dolomitic limestone particles in relation to the polypropylene fiber filter medium. These results implied that the surface porosity of the filter medium interfered in the formation and removal of the formed powder layer, helping or preventing the cleaning of the filter medium. Thus, it was found that the polyester fiber filter media showed the best operating performance with high collection and cleaning efficiency.
Keywords: Filtração de ar; Limpeza jato pulsante; Eficiência do meio filtrante; Tratamento de superfície.; Air filtration; Pulse jet cleaning; Efficiency of the filter medium; Surface treatment; ENGENHARIAS::ENGENHARIA QUIMICA